A wear-resistant insulating composite coating on steel surface and preparation method thereof
By forming a composite coating of graphene-nanoTiN inner layer and nano Al2O3 outer layer on the surface of steel materials, the problem of easy wear and non-insulation of steel materials is solved, significantly improving its wear resistance and insulation performance, and extending service life And expanded the application areas.
Patent Information
- Application Number
- CN202310448121.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-04-24
AI Technical Summary
Steel materials are prone to wear due to low hardness, and the existing surface treatment process cannot simultaneously improve wear resistance and insulation performance, limiting their application in electrical and communication systems.
The composite coating of graphene-nanoTiN inner layer and nano Al2O3 outer layer is used to deposit on the surface of the steel matrix through chemical vapor deposition to form a dense and uniform wear-resistant insulating composite coating, which enhances the bonding force between the matrix and the coating and improves the Wear resistance and insulation properties.
It significantly improves the wear resistance and insulation properties of steel materials, extends service life, and expands its application range in electronics, electrical appliances, aerospace and other fields.
Smart Images

Figure CN116536646B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a wear-resistant insulating composite coating on a steel surface and a preparation method thereof. Background Art
[0002] Steel is a general term for iron-carbon alloys with a carbon content between 0.02wt% and 2.11wt%. Steel is usually referred to as steel together with iron. Electromagnetic pure iron is a high-quality steel with an iron content of more than 99.5%. Its components have low carbon, sulfur and phosphorus contents. It has the characteristics of high magnetic induction intensity, low price and simple heat treatment process. It is currently widely used as a soft magnetic material, such as the shell, armature, valve core, movable iron core and other parts of the solenoid valve. However, due to the extremely low content of alloy elements contained in electromagnetic pure iron materials, which is almost zero, and the absence of alloy strengthening phases, its hardness is extremely low. As a structural part or transmission part material, it often suffers from severe material wear due to mutual friction between workpieces, which greatly reduces its service life. In addition, in recent years, steel materials represented by electromagnetic pure iron have gradually been applied to the fields of electrical circuits and communication systems, and their excellent magnetic properties are often limited by their conductivity. Therefore, improving the wear resistance and insulation properties of steel materials such as electromagnetic pure iron is an urgent problem to be solved.
[0003] Existing process methods such as surface nitriding can only improve the wear resistance of steel materials, but cannot achieve insulation protection. At the same time, the surface nitriding process has defects such as thin strengthening layer and weak strengthening effect, and its improvement on the wear resistance of steel materials is still limited.
[0004] A Chinese patent document with publication number CN115261855A discloses a method for preparing a permeation-plating composite coating, wherein the method sequentially performs degreasing and cleaning, preheating treatment, nitriding layer preparation, secondary cleaning, surface activation, electroplating of chromium layer, cleaning and drying treatment on a steel substrate, and improves the overall comprehensive performance of the substrate surface coating under extreme working conditions of high temperature, high frequency, high pressure impact or extrusion wear by combining the permeation layer with the plating layer, thereby ensuring the service life of the component and avoiding the performance degradation of the component due to long-term wear; a Chinese patent document with publication number CN107904590A discloses a method for preparing an Al-Al2O3 composite coating with high corrosion resistance and high wear resistance suitable for the surface of a steel material, wherein the invention coats an aluminum base layer on the surface of the steel material, wherein the components of the aluminum base layer include aluminum and Al2O3, and further adopts a bipolar micro-arc oxidation process to in-situ generate an Al2O3 ceramic layer on the aluminum base layer, thereby solving the problem that it is difficult to take both wear resistance and corrosion resistance into consideration; however, the above methods cannot achieve insulation protection, and the wear resistance needs to be further improved.
[0005] Therefore, in view of the problems of easy wear and non-insulation faced by steel materials in the existing technology, it is urgent to develop a coating with dense and uniform properties, strong bonding force, good wear resistance and insulation, and a preparation method thereof, so as to overcome the shortcomings of the existing surface strengthening process such as thin strengthening layer, poor wear resistance and non-insulation, improve the wear resistance of steel materials and achieve insulation performance, and further expand the application of steel materials. Summary of the invention
[0006] The present invention provides a wear-resistant insulating composite coating on the surface of steel, comprising a graphene-nano TiN inner layer and a nano Al2O3 outer layer. The wear-resistant insulating composite coating has a strong metallurgical bond with the steel substrate, and the coating is dense and uniform, with a controllable structure. It has the advantages of strong bonding, wear resistance, good insulation performance, etc., and can significantly improve the wear resistance and insulation performance of steel, extend its service life and expand its application field.
[0007] The specific technical solutions adopted are as follows:
[0008] A wear-resistant insulating composite coating on the surface of steel comprises a graphene-nano TiN inner layer and a nano Al2O3 outer layer. The thickness of the graphene-nano TiN inner layer is 0.01-1000 μm, and the thickness of the nano Al2O3 outer layer is 0.01-10000 μm.
[0009] The graphene-nano TiN inner layer is composed of one-dimensional graphene and rice-grained TiN crystal grains, the content of graphene is 0.01-1wt%, and the particle size of the TiN crystal grains is 50-300nm.
[0010] The nano-Al2O3 outer layer is composed of blocky Al2O3 grains, and the grain size of the Al2O3 grains is 250-550nm.
[0011] Preferably, the thickness of the graphene-nano TiN inner layer is 0.01-100 μm, and the thickness of the nano Al2O3 outer layer is 0.01-1000 μm; the particle size of the TiN grains in the graphene-nano TiN inner layer is 100-200 nm, and the particle size of the Al2O3 grains in the nano Al2O3 outer layer is 300-400 nm. Under the above preferred thickness and particle size, the composite coating has better bonding strength, wear resistance and insulation performance with the steel substrate.
[0012] Preferably, the friction coefficient of the wear-resistant insulating composite coating on the steel surface is 0.28-0.32, and the average wear rate is 1.6×10 -7 -1.9×10 -7 mm 3 N -1 m -1 , the binding force is 80-125N, and the resistance is 1.7×10 13 -2×1013 Ω, has the advantages of strong bonding, wear resistance and good insulation performance.
[0013] The present invention also provides a method for preparing the wear-resistant insulating composite coating on the steel surface, comprising the following steps:
[0014] (1) pre-treating the substrate, the pre-treatment including cleaning, sandblasting and drying steps;
[0015] (2) depositing a graphene-nano TiN inner layer on the pretreated substrate surface by chemical vapor deposition;
[0016] (3) Depositing a nano-Al2O3 outer layer on the surface of the graphene-nano-TiN inner layer by chemical vapor deposition to obtain the wear-resistant insulating composite coating on the steel surface.
[0017] The present invention enhances the bonding force between the composite coating and the substrate through the synergistic effect between nanomaterials and utilizes the excellent properties of one-dimensional graphene, nano-TiN and nano-Al2O3, thereby significantly improving the comprehensive properties of steel, such as the wear resistance and insulation performance.
[0018] The substrate includes but is not limited to stainless steel, high-speed steel, cast iron, cemented carbide or electromagnetic pure iron, etc.; preferably, the substrate is electromagnetic pure iron.
[0019] Specifically, the pretreatment steps are: cleaning, sandblasting, re-cleaning and vacuum drying the surface of the substrate in sequence.
[0020] Preferably, the cleaning is ultrasonic cleaning; the material used for sandblasting is at least one of white corundum sand (aluminum oxide sand), brown corundum sand, and quartz sand; the vacuum drying conditions are 60-80°C, 10 -2 -10 -1 Pa, 20-60 minutes.
[0021] Further preferably, the ultrasonic cleaning time is 60-120 minutes, and the cleaning reagent is at least one of alcohol, acetone, deionized water, and distilled water.
[0022] In the chemical vapor deposition process of step (2), the titanium source used is at least one of butyl titanate, titanium tetrachloride, titanium trichloride, titanium dichloride, titanium chloride, and titanium powder; the nitrogen source used is at least one of nitrogen, ammonia, nitrogen dioxide, and nitric oxide; the auxiliary gas used is argon and / or hydrogen; the carbon source for generating graphene comes from the carbon of the steel substrate body; the titanium source is loaded into the chemical vapor deposition chamber with the auxiliary gas as a carrier to participate in the reaction.
[0023] Preferably, the titanium source is titanium tetrachloride, the nitrogen source is nitrogen, and the auxiliary gas is hydrogen.
[0024] Preferably, the chemical vapor deposition process parameters of step (2) are: auxiliary gas flow rate is 1500-2500sccm, nitrogen source flow rate is 1000-2000sccm, deposition temperature is 1000-1050°C, heating rate is 5-8°C / min, and deposition time is 120-240min.
[0025] In the chemical vapor deposition process of step (3), the aluminum source used is at least one of aluminum powder, aluminum ingot, aluminum trichloride, and aluminum pentachloride; the auxiliary gas used is at least one of argon, nitrogen, ammonia, and hydrogen; the reaction gas used is at least one of carbon monoxide, carbon dioxide, oxygen, and water vapor; the aluminum source is carried into the chemical vapor deposition chamber with the auxiliary gas as a carrier to participate in the reaction.
[0026] Preferably, the aluminum source is aluminum trichloride, the reaction gas is a mixed gas of carbon monoxide and carbon dioxide, and the auxiliary gas is hydrogen.
[0027] Preferably, the chemical vapor deposition process parameters of step (3) are: auxiliary gas flow rate is 1000-2000sccm, reaction gas flow rate is 100-1500sccm, deposition temperature is 950-1050°C, heating rate is 5-8°C / min, and deposition time is 240-480min.
[0028] Preferably, the cooling step includes first-stage cooling and second-stage cooling; during the first-stage cooling process, the aluminum source and the reaction gas are stopped, the auxiliary gas flow rate is reduced to 300-500sccm, the cooling rate is 3-5°C / min, and the temperature is reduced to 400-450°C; during the second-stage cooling process, when the temperature is reduced to 400-450°C, the auxiliary gas flow rate is reduced to 100-300sccm; when the temperature is reduced to 50-100°C, the auxiliary gas is stopped, and then cooled to room temperature. The present invention adopts a step-by-step cooling method to control the purity and grain size of the coating by controlling the cooling temperature.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The wear-resistant insulating composite coating on the steel surface provided by the present invention comprises a graphene-nano TiN inner layer and a nano Al2O3 outer layer, wherein the graphene-nano TiN inner layer is an intermediate transition layer for alleviating the mismatch in thermal expansion coefficient between the steel and the nano Al2O3 outer layer, and enhancing the bonding force between the coating and the substrate, thereby improving the wear resistance to a certain extent; the nano Al2O3 outer layer can effectively reduce the wear of the coating and give the steel excellent insulating properties.
[0031] (2) The wear-resistant insulating composite coating of the present invention has a strong metallurgical bond with the steel substrate. The coating is dense and uniform with a controllable structure. It has the advantages of strong bonding, wear resistance, and good insulation performance. It can significantly improve the wear resistance and insulation performance of steel materials such as DT-4 electromagnetic pure iron, extend its service life, and expand its application field.
[0032] (3) The wear-resistant insulating composite coating of the present invention has little effect on the dimensional accuracy of the steel substrate, has good adaptability to the substrate shape, and is suitable for the fields of electronics, electrical appliances, aerospace, etc. At the same time, the wear-resistant insulating composite coating has low production cost, simple process, strong controllability, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD test diagram of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0034] Figure 2 This is a Raman spectrum of graphene in the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0035] Figure 3 This is a SEM morphology of the graphene-nano TiN inner layer in the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0036] Figure 4 This is a SEM morphology of the outer layer of nano-Al2O3 in the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0037] Figure 5 This is a cross-sectional SEM morphology of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0038] Figure 6 This is a bonding strength test diagram of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1.
[0039] Figure 7 This is a test chart of the friction coefficient of the wear-resistant insulating composite coating on the surface of the DT-4 electromagnetic pure iron in Example 1.
[0040] Figure 8 This is a test chart of the average wear rate of the wear-resistant insulating composite coating on the surface of the DT-4 electromagnetic pure iron in Example 1.
[0041] Fig. 9 This is a test diagram of the insulation performance of the wear-resistant insulating composite coating on the surface of the DT-4 electromagnetic pure iron in Example 1. DETAILED DESCRIPTION
[0042] The present invention is further illustrated below in conjunction with the examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0043] DT-4 is a grade of electromagnetic pure iron material, and the corresponding national standard is GB6983-2008.
[0044] Example 1
[0045] (1) Pretreatment of DT-4 electromagnetic pure iron substrate: The surface of the DT-4 electromagnetic pure iron substrate with a size of 10mm*10mm*5mm was polished to remove impurities, and then the surface was sandblasted with quartz sand. After sandblasting, it was ultrasonically cleaned with acetone. -2 -10 -1 After vacuum drying for 40 min at 60-80°C, place in a CVD (chemical vapor deposition) reaction chamber;
[0046] (2) Use a two-stage vacuum pump set to evacuate the CVD device to 10 -2 Pa, then introduce hydrogen and argon at the same time, the hydrogen flow rate is 200sccm, the argon flow rate is 200sccm, start the furnace heating program, set the heating rate to 8℃ / min, and the deposition temperature to 1015℃:
[0047] (3) Preparation of graphene-nano TiN inner layer by chemical vapor deposition: The CVD device was heated to 1015°C to enter the coating deposition procedure, titanium tetrachloride (titanium source), nitrogen (nitrogen source) and hydrogen (auxiliary gas) were introduced, and the nitrogen flow rate was 1500 sccm. Titanium tetrachloride was carried into the CVD device with hydrogen as auxiliary gas, and the hydrogen flow rate was 2000 sccm. After a deposition time of 180 min, the deposition of the graphene-nano TiN inner layer was completed;
[0048] (4) Preparation of nano-Al2O3 outer layer by chemical vapor deposition: The CVD device was heated to 1020°C to enter the coating deposition program, and aluminum chloride (aluminum source), carbon dioxide (reaction gas), carbon monoxide (reaction gas) and hydrogen (auxiliary gas) were introduced. The carbon dioxide flow rate was 500 sccm, the carbon monoxide flow rate was 200 sccm, and the deposition time was 300 min. Aluminum chloride was carried into the CVD device with hydrogen as the auxiliary gas, and the hydrogen flow rate was 1600 sccm.
[0049] (5) After the two-step chemical vapor deposition is completed, the CVD device enters a controllable cooling mode, the aluminum source and the reaction gas are stopped, the hydrogen flow rate is reduced to 300-500sccm, the cooling rate is 3-5°C / min, the temperature is cooled to 400-450°C, and then the hydrogen flow rate is reduced to 100-300sccm; when the temperature drops to 50-100°C, the hydrogen flow is stopped, and then cooled to room temperature to obtain a wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron.
[0050] The wear-resistant insulating composite coating comprises a graphene-nano TiN inner layer and a nano Al2O3 outer layer, the thickness of the graphene-nano TiN inner layer is 2-3 μm, the thickness of the nano Al2O3 outer layer is 12-15 μm, the graphene-nano TiN inner layer is composed of graphene and TiN grains, the content of graphene is 0.05wt%, and the particle size of the TiN grains is 100-200nm; the nano Al2O3 outer layer is composed of Al2O3 grains, and the particle size of the Al2O3 grains is 300-400nm.
[0051] Example 2
[0052] In this embodiment, the method for preparing the wear-resistant insulating composite coating on the steel surface is different from that in Embodiment 1 only in that: in step (3), the deposition temperature of the graphene-nano TiN inner layer is 1000°C.
[0053] Example 3
[0054] In this embodiment, the method for preparing the wear-resistant insulating composite coating on the surface of steel is different from that in Embodiment 1 only in that in step (3), the titanium source used is titanium trichloride.
[0055] Example 4
[0056] In this embodiment, the method for preparing the wear-resistant insulating composite coating on the steel surface is different from that in Embodiment 1 only in that: in step (4), the deposition temperature of the nano-Al2O3 outer layer is 1030°C.
[0057] Example 5
[0058] In this embodiment, the method for preparing the wear-resistant insulating composite coating on the surface of steel is different from that in Embodiment 1 only in that in step (4), the reaction gas used is oxygen.
[0059] Comparative Example 1
[0060] In this comparative example, the method for preparing the composite coating on the surface of steel is different from that in Example 1 only in that in step (3), the deposition temperature of the graphene-nano TiN inner layer is 930°C.
[0061] Comparative Example 2
[0062] In this comparative example, the method for preparing the composite coating on the surface of steel is different from that in Example 1 only in that in step (4), the deposition temperature of the nano-Al2O3 outer layer is 900°C.
[0063] Comparative Example 3
[0064] In this comparative example, the method for preparing the composite coating on the steel surface is different from that in Example 1 only in that: in step (3), the titanium source is carried into the chemical vapor deposition chamber with an auxiliary gas as a carrier to participate in the reaction, and the flow rate of the auxiliary gas is 500 sccm.
[0065] Comparative Example 4
[0066] In this comparative example, the method for preparing the composite coating on the steel surface is different from that in Example 1 only in that: in step (4), the aluminum source is carried into the chemical vapor deposition chamber with an auxiliary gas as a carrier to participate in the reaction, and the flow rate of the auxiliary gas is 800 sccm.
[0067] Comparative Example 5
[0068] In this comparative example, the method for preparing the composite coating on the surface of steel is different from that in Example 1 only in that in step (4), the flow rate of the reaction gas CO2 is 2000 sccm.
[0069] Sample analysis
[0070] The wear-resistant insulating composite coating obtained in Example 1 and composited on the surface of DT-4 electromagnetic pure iron was tested by XRD, SEM, bonding strength, friction and wear properties, and insulation properties.
[0071] (1) Morphology and structure analysis
[0072] Figure 1 This is the XRD test diagram of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1. Figure 1 The results show that the wear-resistant insulating composite coating is composed of TiN phase and Al2O3 phase. Due to the extremely low content of graphene, XRD cannot detect it. The graphene in the wear-resistant insulating composite coating was further characterized. The results are as follows Figure 2 As shown in the Raman spectrum, the typical D peak, G peak and 2D peak of graphene are located at 1579-1588cm -1 The G peak originates from the stretching vibration of sp2 hybrid atoms in graphene and is located at 2688-2699 cm -1 The 2D peak originates from the double-phonon resonance process, and the D peak at 1350cm-1 originates from the destruction of the originally static state of carbon atoms.
[0073] Figure 3 This is a SEM morphology of the graphene-nano TiN inner layer in the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1. Figure 3 The results show that the inner surface of the graphene-nano TiN layer is dense and uniform, and contains TiN grains with a rice-grain shape. The rice-grain-shaped grains are aggregated and piled together, and the grain size is 100-200nm.
[0074] Figure 4 This is the SEM morphology of the outer layer of nano-Al2O3 in the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1. Figure 4 The results show that the outer surface of nano-Al2O3 is dense and uniform, and the coating is composed of massive Al2O3 grains with a grain size of 300-400nm.
[0075] Figure 5 This is a cross-sectional SEM morphology of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron in Example 1. Figure 5 The results show that the wear-resistant insulating composite coating is tightly bonded to the DT-4 electromagnetic pure iron, the thickness of the graphene-nano TiN inner layer is 2-3μm, the thickness of the nano Al2O3 outer layer is 12-15μm, and the total thickness of the wear-resistant insulating composite coating is 14-18μm.
[0076] (2) Performance testing
[0077] (2.1) Test method for coating bonding performance: The coating-base material bonding performance was tested using the Revetest scratch test system. Test mode: Rockwell round diamond tip with a curvature radius of 0.2 mm was used. The scratch length was 3 mm, the scratch rate was 3 mm / min, the test load range was 1 N to 150 N, and the loading rate was 99 N / min. Each sample was tested 3 times, and the average of the results was taken.
[0078] The wear-resistant insulating composite coating of Example 1 composited on the surface of DT-4 electromagnetic pure iron was tested for coating bonding performance. The results are as follows: Figure 6 As shown, the bonding force between the wear-resistant insulating composite coating and the DT-4 electromagnetic pure iron substrate is 118.5N.
[0079] (2.2) Friction performance test method: The wear resistance of the sample was tested using an Rtec friction and wear tester. The test mode was to use a 6mm SiC ball to perform XY bidirectional linear non-lubricated reciprocating friction on the sample at room temperature. The specific test parameters were: normal load 5-20N, friction speed 20mm / s, friction distance 5mm, time 20min, frequency 2Hz. Each sample was tested 3 times and the average of the results was taken.
[0080] The friction performance test of the wear-resistant insulating composite coating of Example 1 on the surface of DT-4 electromagnetic pure iron was carried out. The results are as follows: Figure 7 As shown, the friction coefficient of the wear-resistant insulating composite coating is measured to be 0.28.
[0081] (2.3) Wear performance test method: Based on the friction performance test, the wear scar volume test is first performed by using a surface profiler to obtain the wear scar volume data; secondly, the wear scar volume data is integrated and calculated by the analysis software to obtain the wear scar volume value; finally, the wear rate is calculated according to the wear rate calculation formula:
[0082]
[0083] Where, W: volume wear rate; V: wear volume; S: load size; L: total friction distance.
[0084] The wear resistance and insulation composite coating of Example 1 on the surface of DT-4 electromagnetic pure iron were tested. The results are as follows: Figure 8 As shown in Figure 2, the average wear rate of the wear-resistant insulating composite coating is 1.6×10 -7 mm 3 N -1 m -1 .
[0085] (2.4) Insulation performance test method: Use a Keithley power meter model 4200-SCS / F to test the maximum resistance of the material by continuously increasing the voltage until the material is broken down. The maximum resistance value when the material is broken down is used to characterize the insulation performance of the material.
[0086] The insulation performance of the wear-resistant insulating composite coating composited on the surface of DT-4 electromagnetic pure iron in Example 1 was tested. The results are as follows: Fig. 9 As shown, the resistance of the wear-resistant insulating composite coating is 2×10 13 Ω.
[0087] (3) Comparison of test results of composite coatings prepared in Examples 1-5 and Comparative Examples 1-5
[0088] The grain morphology, grain size, bonding force, friction coefficient, wear rate and insulation performance of the composite coatings in Examples 2-5 and Comparative Examples 1-5 were tested according to the above method. The results are shown in Table 1.
[0089] Performance test results of the composite coatings prepared in Examples 1-5 and Comparative Examples 1-5
[0090]
[0091] It can be seen from Table 1 that when the chemical vapor deposition parameters of the graphene-nano TiN inner layer are changed, the grain size of the graphene-nano TiN inner layer of the wear-resistant insulating composite coating composited on the surface of DT-4 electromagnetic pure iron prepared in the embodiment (the inner layer TiN grain size is 230-300nm in Example 3) is significantly smaller than the composite coating prepared in the comparative example (such as the inner layer TiN grain size is 800-1200nm in Comparative Example 3); when the chemical vapor deposition parameters of the nano Al2O3 outer layer are changed, the grain size of the nano Al2O3 outer layer of the wear-resistant insulating composite coating composited on the surface of DT-4 electromagnetic pure iron prepared in the embodiment (the outer layer Al2O3 grain size is 450-550nm in Example 4) is significantly smaller than the composite coating prepared in the comparative example (such as the outer layer Al2O3 grain size is 1200-1500nm in Comparative Example 5).
[0092] The bonding strength of the wear-resistant insulating composite coating prepared in Examples 1-5 and compounded on the surface of DT-4 electromagnetic pure iron (the bonding strength of the composite coating in Example 3 is 109N) is significantly greater than that of the composite coating prepared in Comparative Examples 1-5 (such as the bonding strength of the coating in Comparative Example 1 is 65N).
[0093] The friction coefficient of the wear-resistant insulating composite coating prepared in Examples 1-5 and compounded on the surface of DT-4 electromagnetic pure iron (the friction coefficient in Example 3 is 0.32) is significantly smaller than the composite coating prepared in Comparative Examples 1-5 (such as the friction coefficient in Comparative Example 1 is 0.35).
[0094] The wear rate of the wear-resistant insulating composite coating on the surface of DT-4 electromagnetic pure iron prepared in Examples 1-5 (the wear rate in Example 3 is 1.9×10 -7 mm 3 N -1 m -1 ) is significantly smaller than the composite coatings prepared in Comparative Examples 1-5 (for example, the wear rate in Comparative Example 1 is 4.9×10 -5 mm 3 N -1 m -1 ).
[0095] The insulation performance of the wear-resistant insulating composite coating prepared in Examples 1-5 and composited on the surface of DT-4 electromagnetic pure iron (the insulation performance of the coating in Example 3 is 1.7×10 13 Ω) is significantly greater than the composite coatings prepared in Comparative Examples 1-5 (for example, the insulation performance of the coating in Comparative Example 1 is 6.3×10 9 Ω).
[0096] Therefore, compared with comparative examples 1-5, the wear-resistant insulating composite coatings prepared in examples 1-5 of the present invention and compounded on the surface of DT-4 electromagnetic pure iron have excellent bonding performance, friction and wear resistance, and insulation performance.
[0097] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A wear-resistant insulating composite coating on a steel surface, characterized in that: It includes a graphene-nano TiN inner layer and a nano Al2O3 outer layer, wherein the thickness of the graphene-nano TiN inner layer is 2-3 μm, and the thickness of the nano Al2O3 outer layer is 12-15 μm; The graphene-nano TiN inner layer is composed of graphene and TiN grains, the graphene content is 0.01-1 wt %, and the particle size of the TiN grains is 100-300 nm; The outer layer of nano-Al2O3 is composed of Al2O3 grains, and the particle size of Al2O3 grains is 300-550 nm.
2. The wear-resistant insulating composite coating on steel surface according to claim 1, characterized in that: The particle size of TiN grains in the graphene-nano-TiN inner layer is 100-200 nm, and the particle size of Al2O3 grains in the nano-Al2O3 outer layer is 300-400 nm.
3. The method for preparing the wear-resistant insulating composite coating on the steel surface according to claim 1 or 2, characterized in that: The following steps are involved: (1) Pretreatment of the substrate, including cleaning, sandblasting and drying steps; (2) depositing a graphene-nano TiN inner layer on the surface of the pretreated substrate by chemical vapor deposition; in the chemical vapor deposition process of step (2), the titanium source used is at least one of butyl titanate, titanium tetrachloride, titanium trichloride, titanium dichloride, titanium chloride, and titanium powder; the nitrogen source used is at least one of nitrogen, ammonia, nitrogen dioxide, and nitric oxide; the auxiliary gas used is argon and / or hydrogen; (3) depositing a nano-Al2O3 outer layer on the surface of the graphene-nano-TiN inner layer by chemical vapor deposition, and obtaining the wear-resistant insulating composite coating on the steel surface after cooling; in the chemical vapor deposition process of step (3), the aluminum source used is at least one of aluminum powder, aluminum ingot, aluminum trichloride, and aluminum pentachloride; the auxiliary gas used is at least one of argon, nitrogen, ammonia, and hydrogen; the reaction gas used is at least one of carbon monoxide, carbon dioxide, oxygen, and water vapor.
4. The method for preparing the wear-resistant insulating composite coating on the steel surface according to claim 3, characterized in that: The pretreatment steps are: cleaning, sandblasting, re-cleaning and vacuum drying the surface of the substrate in sequence.
5. The method for preparing the wear-resistant insulating composite coating on the steel surface according to claim 3, characterized in that: The chemical vapor deposition process parameters of step (2) are: the flow rate of the auxiliary gas is 1500-2500 sccm, the flow rate of the nitrogen source is 1000-2000 sccm, the deposition temperature is 1000-1050 °C, and the deposition time is 120-240 min.
6. The method for preparing the wear-resistant insulating composite coating on the steel surface according to claim 3, characterized in that: The chemical vapor deposition process parameters of step (3) are: the flow rate of the auxiliary gas is 1000-2000 sccm, the flow rate of the reaction gas is 100-1500 sccm, the deposition temperature is 950-1050 °C, and the deposition time is 240-480 min.
Citation Information
Patent Citations
Surface composite coating of steel and iron materials and preparation method thereof
CN107904590A
Preparation method of diffusion coating composite coating
CN115261855A
Coated tool
CN105517738A
Preparation method of high binding force multistage hard coating
CN106086802A